Improving shear bond strength of metallic brackets after whitening - Aristizábal,Juan Fernando (2020)
ABSTRACT Objective: To evaluate a protocol for bonding metallic brackets after bleaching with hydrogen peroxide (HP). Methods: 60 extracted maxillary premolar were randomly divided into an unbleached control group and two groups bleached with a solution of 35% hydrogen peroxide prior to bonding. The teeth in one of the treated groups were bonded immediately after bleaching; while the other group was treated with 10% sodium ascorbate immediately after bleaching and before bonding. The teeth in all groups were stored in an artificial saliva solution for 7 days after bonding. The shear bond strength data was measured in megapascals (MPa) and the fail attempts were verified. The significance level was established at p< 0.05. Results: The unbleached group, in which brackets were bonded to untreated enamel, had the highest bond strength values (11.0 ± 5.7MPa) in comparison to the bleached group (7.14 ± 40MPa), in which brackets were bonded to recently bleached enamel. Slightly improved bond strength was observed in the antioxidant group (8.13 ± 5.4MPa), in which the teeth were bleached and then the antioxidant was applied to the teeth before bonding. Unbleached and bleached groups showed statistically significant difference for shear bond strength (p=0.03) and load strength (p=0.03); no significant differences were noted between unbleached and antioxidant groups (p=0.52). Conclusion: The antioxidant treatment applied immediately after bleaching was effective in reversing the reduction in shear bond strength of brackets after tooth bleaching.